(5x+10)=(6x-1)

Simple and best practice solution for (5x+10)=(6x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+10)=(6x-1) equation:


Simplifying
(5x + 10) = (6x + -1)

Reorder the terms:
(10 + 5x) = (6x + -1)

Remove parenthesis around (10 + 5x)
10 + 5x = (6x + -1)

Reorder the terms:
10 + 5x = (-1 + 6x)

Remove parenthesis around (-1 + 6x)
10 + 5x = -1 + 6x

Solving
10 + 5x = -1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
10 + 5x + -6x = -1 + 6x + -6x

Combine like terms: 5x + -6x = -1x
10 + -1x = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
10 + -1x = -1 + 0
10 + -1x = -1

Add '-10' to each side of the equation.
10 + -10 + -1x = -1 + -10

Combine like terms: 10 + -10 = 0
0 + -1x = -1 + -10
-1x = -1 + -10

Combine like terms: -1 + -10 = -11
-1x = -11

Divide each side by '-1'.
x = 11

Simplifying
x = 11

See similar equations:

| x-8/x2 | | x-5/x4 | | 0.19x-3.3=0.57x+0.17 | | 4/12=v/9 | | F(x)=4x^2-9x-7 | | (3/2x^(1/2))-3x=0 | | 3x-4+(9-5)=3x(4-2)+5 | | -2e^2x=-44 | | (3/2x^1/2)-3x=0 | | 10p+24=38 | | 3/2x^1/2-3x=0 | | 5cosx=6.5-12sinx | | y=250x+.10 | | 4/√3 | | F=on | | (a/-4)=1 | | 32+(-14)= | | 3x-10(x+2)=169-7x | | A/3-5=12 | | 14x+28=4 | | 2a+3c-a-c= | | 6(2x-3)-3x=5x+8 | | 9x^2+4y^2-8y-32=0 | | 5x=-3.7 | | 7x-5=27 | | 9y=5y+5-9 | | An+c=5 | | b/8=9/5 | | 7x-2=7-17 | | 3l+6=p | | 2(y-5)-5=3 | | (x/4)-2x=2 |

Equations solver categories